Ler e escrever em filosofia no ensino médio em tempos de tecnologias digitais - Moraes, Simone Becher Araujo (2018)
The context of this research revolves around the current configuration of our increasingly technological society, which has effects in school and in teaching and learning philosophy in the context of high school. This technological reality characterized by easy and quick access to information of all kinds, has been modifying cognitive processes and causing changes in the reading, writing ways and knowledge producing. Thus, in times of hyperconnection and hypertext, teaching and learning to Reading and Writing in Philosophy (RWP) are real challenges. The philosophy class, in the last 20 years, has been the meeting place between the new - the young called diginal natives - and the traditional - philosophy, its theories, thinkers and methods. It was thinking in these new configurations that we sought in this doctoral research, to understand how, in times of Digital Technologies (DT) it may be possible to teach and learn Reading and Writing in Philosophy in high school. In order to answer this question or at least trying to establish some reflections and some tensions, it was determined as the central corpus of the research, texts of researchers and philosophy professors that was published in two important events of the area: the South-Brazilian Symposium on the Philosophy Teaching published between the years of 2002 and 2010 and the texts of the Proceedings of the GT - Philosophy and Philosophy Teaching of the National Association of Postgraduate Studies - published between the years 2013 and 2017. As other materialities used to give more support to the reflections proposed here, some thinkers of technologies such as Lévy (1993, 1999, 2017) were brought in; Serres (2013); Lipovetsky (2004, 2005), and also thinkers of philosophy, such as Fabbrini (2005); Hadot (1995); Havelock (1996); Cossutta (2001), among others. In addition to the theoretical reflections based on the authors of the corpus, we present in this thesis the courses and results of an investigative experiment carried out with high school students. In this investigative experiment, two Digital Technologies were used for RWP teaching and learning, namely Google Docs and the Facebook Group. As conclusions of this research, it was possible to confirm that LEF are, in fact, challenging skills and abilities to be pursued in high school and that they raise discussions around at least five angles pointed by the analyzed authors: 1) From the angle of the numerous needs and gaps in the training of philosophy teachers for RWP teaching; 2) From the perspective of the consequences and effects of Public Policies for Education within the scope of philosophy teaching; 3) From the angle of RWP methodologies that make working with texts a practice endowed with specificities and, consequently, a challenging activity in high school, especially when young people have habits and practices of reading and writing so different from those required in the philosophical tradition; 4) From the angle of the limitations and potentialities that the DT present to teaching and learning RWP, and, 5) From the angle of the propositions and confrontations suggested by the analyzed authors that searched for new ways for RWP teaching using DT in high school. It was also concluded that Digital Technologies can serve as allies in teaching and learning practices of Reading and Writing in Philosophy but are not alone enough to meet the students learning needs and lacks, who, although they have an easy way to use the tools they need guidance to use them properly so that they can, in a qualified and meaningful way, learn Reading and Writing in Philosophy. This research was carried out within the research line of School Practices and Public Policies of the Graduate Program in Education of the Federal University of Santa Maria, with financial support from the Social Demand Program (DS-CAPES), as well as the Doctoral Program Sandwich Abroad (PDSE-CAPES).